Minimally invasive microwave ablation provides excellent long‐term outcomes for otherwise inaccessible hepatocellular cancer. Issue 8 (8th April 2020) - Altman, Ariella M.; Coughlan, Alexandria; Shukla, Dip M.; Schat, Robben; Spilseth, Benjamin; Marmor, Schelomo; Hui, Jane Y. C.; Tuttle, Todd M.; Jensen, Eric H.
Abstract: Background and Objectives: Thermal ablation can be used as a bridge to transplant or with curative intent for hepatocellular carcinoma (HCC). We report our experience with laparoscopic ablation of HCC in patients deemed inaccessible by the percutaneous approach. Methods: We performed a retrospective review of surgical ablations from 2009 to 2017. Patient demographics, disease and treatment characteristics, and outcomes were abstracted from the medical record. Kaplan‐Meier modeling was performed for survival and recurrence. Results: Thirty‐three patients were included with a median age of 62 (interquartile range [IQR], 57‐67). Most patients were male (76%) and Caucasian (70%). Ninety‐seven percent had underlying cirrhosis. Median model for end stage liver disease‐sodium was 9.5 (IQR, 8‐12). The median maximal diameter of ablated lesions was 2.6 cm (IQR, 1.8‐3.0). Thirty‐nine lesions were ablated; 97% were completed laparoscopically. The median maximal diameter of the ablation zone was 4.8 cm (IQR, 3.8‐5.7) with a median difference of ablation zone to the tumor of 2.0 cm (IQR, 1.5‐2.75). Twelve patients received additional treatment. Median disease‐free survival was 66.7 months and median follow‐up 42.9 months. Disease recurrence occurred in 13 patients (39%)—systemic recurrence in 6%, intrahepatic recurrence in 27% and local recurrence in 6%. Conclusion: Laparoscopic thermal ablation of HCC is safe and provides good oncologic outcomes for otherwise inaccessible tumors.